2013
DOI: 10.4161/epi.23366
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation profiles in the premature aging disorders Hutchinson-Gilford Progeria and Werner syndrome

Abstract: DNA methylation gradiently changes with age and is likely to be involved in aging-related processes with subsequent phenotype changes and increased susceptibility to certain diseases. The Hutchinson-Gilford Progeria (HGP) and Werner Syndrome (WS) are two premature aging diseases showing features of common natural aging early in life. Mutations in the LMNA and WRN genes were associated to disease onset; however, for a subset of patients the underlying causative mechanisms remain elusive. We aimed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 21 publications
3
61
0
1
Order By: Relevance
“…BAF interacts with several partners, among them A-and B-type lamins, NuMA, and influences active or silencing marks of histones [269,270]. Aberrant DNA methylation profiles, in particular targeting the NFB signaling pathway, are among the other epigenetic modifications in cells from HGPS and Werner syndrome patients [271].…”
Section: Dna Replication Transcription Repair and Epigenetic Defectmentioning
confidence: 99%
“…BAF interacts with several partners, among them A-and B-type lamins, NuMA, and influences active or silencing marks of histones [269,270]. Aberrant DNA methylation profiles, in particular targeting the NFB signaling pathway, are among the other epigenetic modifications in cells from HGPS and Werner syndrome patients [271].…”
Section: Dna Replication Transcription Repair and Epigenetic Defectmentioning
confidence: 99%
“…More recently, it has been observed that CpG sites in HGPS cells gain methylation when compared to hypomethylated control regions but lose methylation when compared to hypermethylated control regions [23]. Again, the trend is a homogeneous redistribution of epigenetic markers in HGPS specimens.…”
Section: Dna Methylationmentioning
confidence: 91%
“…Vogt -Koyanagi -Harada disease is a bilateral, chronic, diffuse granulomatous uveitis with poliosis, vitiligo, central nervous system, and auditory signs. Many researchers, especially Yang's group, have investigated the gene polymorphisms of many factors including IL-17 that are associated with Vogt -Koyanagi -Harada disease in a Chinese Han population (Shu et al 2010) since Yakura et al first reported the HLA-D locus linkage (Yakura et al 1976 (Heyn et al 2013). …”
Section: Acquired Hypopigmentation Disordersmentioning
confidence: 99%